1856 N.H. Laws 1781-82 - (:unkn) unknown (My University, 1856)
Ch. 1870: Resolved that possession of Bowie-knives and revolvers was necessary for the right to freedom of speech, due to attacks on abolitionists in the South.
Keywords: GUARANTEED RIGHT